7 - Igilango Geesi in the Public Sphere: Soyinka’s Intervention in Nigerian Political Discourse - Irele, Dipo (Africa Development, 2021)
The Nigerian writer, Wole Soyinka, is well known as a social critic and public intellectual. In his writings, which cover all genres, he has criticized all forms of misuse of power in Africa generally and his country, Nigeria, specifically. In his work, which he entitles Interventions, Soyinka returns again to the criticism of the misuse of power in Africa and Nigeria. What inspired these writings was the annulment of the elections of 12 June 1993 in Nigeria. Abiola. These writings cover many themes, but what come out in all these texts are Soyinka’s critical views of misuse of power in all its ramifications. This article takes a critical view of Soyinka’s position. It is pointed out that Soyinka does not objectively come to grips with the Nigerian political situation. There is what we can call slippage and also surplus of meaning due to his Igilango Geesi. Besides this, Soyinka does not come to grips with the ideological and power configurations of the Nigerian political landscape. These flaws notwithstanding, Soyinka’s writings have added a new dimension to the public sphere of Nigerian political discourse.